Income support for parents of children with chronic conditions and disability: where do we draw the line? A policy review. Issue 6 (22nd November 2021) - Chua, Clara; Bull, Claudia; Callander, Emily Joy
Abstract : Objective: The aim of this review was to identify and describe whether parents who have had to stop paid employment to care for a child with a chronic condition or disability are eligible for unemployment, family and children, and disability and carer government-provided financial benefits. Design: Policy review. Setting: Group of seven high-income countries. Main outcome measures: All policies related to unemployment, family and children, and disability and carer benefits were included. Information regarding the policy type and description, parent/carer qualification, amount of financial support payable, eligibility criteria and information source were extracted. Payment schedules were converted into 2020 US dollars, using Purchasing Power Parities. Maximum monthly benefit payments were compared with standardised per capita monthly costs of living to determine payment support suitability. Results: Fifty-eight policies relevant to unemployment, family and children, and disability and carer benefit supports were identified. Germany had the highest number of welfare policies for individuals not in employment (n=11), followed by the USA (n=6). Parents or carers of children with chronic conditions or disability who were not in employment qualified for 31 of the 58 policies (53.4%). Most policies required a child to have an impaired ability to function, not just a chronic condition or disability. Conclusions: Greater support for parents and carers to continue their paid employment alongside caring responsibilities is necessary. Graded benefit schedules will also be critical to supporting the spectrum of childhood chronic conditions and disability, and the subsequent spectrum of caring responsibility. Abstract : International comparisons of income support policies across seven nations show unemployed parents or carers of children with chronic conditions or disability qualified for 32 of the 58 policies. Most policies required a child tohave an impaired ability to function, not just a chronic condition or disability.